A preliminary clinico-mycological study of dermatophytes infection - Tiwari, Shivanshi; Kumar, Deepesh (International Journal of Research in Medical Sciences, 2018)
Background: Superficial fungal infections are the most common skin diseases, affecting millions of people throughout the world. Aim of the study was carried out to find, the effect of seasonal variation and socio-economic status on the prevalence of dermatophytes. Methods: A total of fifty clinically suspected cases of dermatophytosis were subjected to mycological studies. Results: Out of which 32 (64%) were culture positive Tinea corporis was the most common clinical type followed by Tinea cruris. Tricophoton rubrum 17/32 (53.12%) was the most common isolate followed by T. mentagrophytes 9/32(28.12%), T. tonsurans 3/32(9.37%), T. verrrucosum 2/32(6.25%) and T. schoenleinii 1/32(3.12%). Most of the patients belonged to the middle socio-economic group (28/50) followed by lower socio-economic group (19/50) maximum cases of dermatophytosis were reported from June to August revealing the fact that hot and humid weather during the monsoons has a great impact on the occurrence of dermatophytosis. Conclusions: It may therefore be concluded that dermatophytosis is now a days a serious public health problem in view of its high occurrence in the world wide population.